PENGARUH ROA, ROE, TOTAL REVENUE, DAN BI RATE TERHADAP SAHAM PADA SEKTOR TRANSPORTASI TAHUN 2009-2014 - Devinta Nur Arumsari (Universitas Negeri Medan, 2015)
This research aims to test the influence of ROA, ROE, The Total Revenue and the BI rate towards the transport sector stocks. The sample of this research is the transportation company registered in BEI in 2009-2014 and is chosen by the method of random sampling. The data used are the panel data with secondary data typescollected by the method documentation. Hypothesis testing is done by the method of multiple regression analysis that views of R-Squared with e-views program results showed that ROA, ROE, Total Revenue doesn’t have a significant influence on the price of the shares, while BI Rate has a significant influence on the price of the stock. This research contributes to the development of the capital market in particularscience-related stock price.